Maternal mortality in Peru, responsibility. - Távara, Luis (2015)
By lower absolute number of maternal deaths in relation to infant deaths, the true dimension of this tragedy was not valued until after after the world conference in Geneva and Nairobi in 1985 and 1987 respectively, after which generated in the world, fortunately, a current safe motherhood. UNICEF estimates that each year 585 000 women die worldwide as a result of complications arising during pregnancy, childbirth and puerperio1. Of all these deaths, 7% (35000) occurs in Latin America and, of these, around 5000 for the Andean Group (Bolivia, Colombia, Ecuador, Peru and Venezuela). I should add that, of these deaths, approximately 1600 for the Peru.